Using Artificial Intelligence (AI) in Developing Marketing Strategies - Sri Handila Mirwan; Puti Lenggo Ginny; Dirmansyah Darwin; Rahmat Ghazali; Meldilianus N J Lenas (International Journal of Applied Research and Sustainable Sciences, 2023)
This research explores the application of artificial intelligence (AI) in contemporary marketing strategies. Through case analysis of leading companies, the study uncovers how AI contributes to market data analysis, marketing personalization, trend forecasting, marketing process automation, recommendation systems, and chatbot development. Data was collected by studying existing literature and analyzing case studies of companies such as Amazon, Netflix, Starbucks, Spotify, Alibaba, and Sephora. The results show that using AI in marketing improves operational efficiency, enriches the customer experience, and increases engagement and loyalty